HUBUNGAN ANTARA PIJAT DIARE DENGAN INTENSITAS DIARE PADA BALITA DI WILAYAH PUSKESMAS MIJEN SEMARANG - Hamidatu Faishara; Nella Vallen Ika Puspita; Mudy Oktiningrum (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Refers to a study conducted in 2006 at an orphanage in Ecuador to determine how massage therapy can reduce the incidence of diarrhea and morbidity, whereas massage therapy is considered safe and beneficial in reducing the consumption of anti-diarrhea medication. This research aims to find out the benefit of diarrhea massage to diarrhea intensity on toddlers. The research uses Pearson Correlation with a one-group pretest-posttest design approach. The toddlers under 5 years old at Puskesmas Mijen, Kota Semarang are taken to be the population in this research. This research uses a total sampling technique, with a sample of 12 toddlers. The technique of data collection uses a demographic questionnaire. The technique of data analysis is conducted by Pearson Correlation test. The result of this research found that the significance of the diarrhea massage to diarrhea intensity for toddlers at Puskesmas Mijen, Semarang is 0,001 (pvalue>0,05). The intensity of diarrhea in children under five after diarrhea massage was experienced by as many as 2 toddlers (16.7%), the intensity of diarrhea is rare in as many as 6 toddlers (50.0%), and the intensity of normal diarrhea occurs in 4 toddlers (33.3%), so it can be concluded that there is a relationship between diarrhea massage and the intensity of diarrhea in toddlers at Puskesmas Mijen Semarang. Keywords: Diarrhea massage, Diarrhea intensity, Toddlers